Implementing the teams games tournament (TGT) cooperative learning model to enhance student learning outcomes on diversity is beautiful - Sarmila; Meriza Faradilla; Khairul Rizal (International Journal of Advances in Educational Research, 2024)
This study aims to improve student learning outcomes on "Diversity is Beautiful" by implementing the Teams Games Tournament (TGT) cooperative learning model at SD Negeri Lamklat, Aceh Besar. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 25 fourth-grade students. Data were collected using learning outcome tests, student activity observation sheets, and interviews. The findings showed significant improvements in student learning outcomes from cycles I to II. In cycle I, the average student score was 72, with a mastery level of 68%. In cycle II, the average score increased to 85, with a mastery level of 92%. Student learning activities also improved, marked by tremendous enthusiasm and active participation in the learning process. The TGT model provided a fun learning experience, motivating students to engage in healthy competition, collaborate in groups, and appreciate diversity. Based on the findings, it is concluded that implementing the TGT cooperative learning model effectively enhances student learning outcomes on the topic "Diversity is Beautiful."